Susceptibility of the "penicillinase-resistant" penicillins and cephalosporins to penicillinase of Staphylococcus aureus. Issue 1 (January 1977) - Lacey, R W; Stokes, A
Abstract : The activities of some semisynthetic penicillins and cephalosporins have been tested against clinical strains of Staphylococcus aureus. The apparent activity in vitro varies with the method of testing used. Determination of MICs using light inocula fails to detect the destructive effect of penicillinase on the antibiotic. This was, however, demonstrated reproducibly by the use of a technique in which a heavy inoculum was pre-incubated for two hours before application of antibiotic to wells. This method of testing probably represents most of the clinical situations in which the drugs are used since both in vitro and in vivo a growing culture is exposed to an antibiotic gradient. Flucloxacillin was inactivated by penicillinase considerably more than either methicillin, cloxacillin, or nafcillin. Cephaloridine was the most vulnerable of the cephalosporins. Cephazolin, cephalothin, and cephalexin were intermediate. Cephradine was the least hydrolysed by staphylococcal penicillinase. It is recommended that the activities of all penicillins and cephalosporins against staphylococci should be tested by diffusion at 37 degrees C with pre-incubation of the culture for two hours at this temperature.